Important Regulatory Guidelines on Natural Products - Sahu, Abhisar; Srivastava, Nimisha; Jena, Devashish; Singh, Aayushee; Kumar, Satya; Chauhan, Iti (Current Traditional Medicine, 2024)
Ayurvedic cosmeceuticals are alluded to as products of various passable magnificence substances to shape the base in which one or more ayurvedic parts are utilized to give benefits and various ailments. The Drugs and Cosmetics Act of 1940 controls the approaches concerning the making, dealing, amassing, allotment, and importing of drugs in essentially a comparable manner to radiance care things in India. Quality control and assessment of Ayurvedic drugs must ensure the effectiveness of the drug. Given their crucial role, it involves evaluating their physical, chemical, and physiochemical qualities, as well as conducting in-vitro and in-vivo tests. Natural ingredients have consistently been our primary source of medicines, and dosage forms determine how drug molecules or plant components are delivered to the site of action within the body. Good agricultural and collection practices (GACP) rules have been given by the WHO (World Health Organization) for the differentiation and planning of regular items. There are primarily two legal regulatory bodies within the AYUSH (Ayurveda, Yoga and Naturopathy, Unani, Siddha, and Homeopathy) sector i.e., Central Council of Indian Medicine (CCIM) and the Central Council of Homeopathy.
Keywords: WHO